Patient-reported symptoms on the antiretroviral regimen efavirenz/emtricitabine/tenofovir. - Edelman, E Jennifer; Gordon, Kirsha; Rodriguez-Barradas, Maria C; Justice, Amy C (AIDS patient care and STDs, 2012)
Most patients (80-90%) newly diagnosed with HIV are started on the antiretroviral regimen efavirenz, emtricitabine, and tenofovir (EFV/FTC/TDF). Existing studies of patient tolerability, however, are limited. We compared symptom experiences of patients on EFV/FTC/TDF, and the subsequent impact on health-related quality of life, with those of patients on other combination antiretroviral therapy (cART). We conducted a cross-sectional analysis of the Veterans Aging Cohort Study from February 2008 to August 2009 to compare the symptom experiences of patients on EFV/FTC/TDF vs. other cART, unadjusted and then adjusted for treatment characteristics, and comorbid disease severity. We then assessed the association between EFV/FTC/TDF use and health-related quality of life. Among the 1,759 patients in our analytic sample, EFV/FTC/TDF use was associated with fewer symptoms than was other cART. The use of EFV/FTC/TDF was independently associated with health-related quality of life, and this association was at least partially explained by symptom burden.
Keywords: Adenine; Anti-HIV Agents; Benzoxazines; Cohort Studies; Cross-Sectional Studies; Deoxycytidine; Drug Therapy, Combination; Female; Health Status; HIV Infections; Humans; Male; Middle Aged; Organophosphonates; Quality of Life; Severity of Illness Index; Treatment Outcome; Veterans